2015
DOI: 10.1183/13993003.00814-2015
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to organic solvents: a risk factor for pulmonary veno-occlusive disease

Abstract: Pulmonary veno-occlusive disease (PVOD) is a rare form of pulmonary hypertension characterised by predominant remodelling of pulmonary venules. Bi-allelic mutations in the eukaryotic translation initiation factor 2α kinase 4 (EIF2AK4) gene were recently described as the major cause of heritable PVOD, but risk factors associated with PVOD remain poorly understood. Occupational exposures have been proposed as a potential risk factor for PVOD, but epidemiological studies are lacking.A case-control study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 39 publications
2
71
0
8
Order By: Relevance
“…Occupational exposure to organic solvents was more frequent in men and in the older age group. The questionnaire also revealed a significantly higher tobacco exposure in PVOD compared to PAH patients (total packyears 33 ± 24.7 vs 8.0 ± 14.3 respectively) [5]. [19].…”
Section: Occupational Dependence Of Pvod/pchmentioning
confidence: 85%
See 3 more Smart Citations
“…Occupational exposure to organic solvents was more frequent in men and in the older age group. The questionnaire also revealed a significantly higher tobacco exposure in PVOD compared to PAH patients (total packyears 33 ± 24.7 vs 8.0 ± 14.3 respectively) [5]. [19].…”
Section: Occupational Dependence Of Pvod/pchmentioning
confidence: 85%
“…A case control study conducted among 33 consecutive PVOD patients and 65 PAH patients as controls revealed significantly higher prevalence of occupational exposure to organic solvents in PVOD patients, compared to PAH patients (72.7% vs 27.7%, respectively). Exposure to trichloroethylene was significantly more frequent in PVOD compared to PAH (42% vs 3%, respectively) [5]. The trichloroethylene use was reported mostly by: metal workers, mechanics and repairers, building painters and cleaners.…”
Section: Occupational Dependence Of Pvod/pchmentioning
confidence: 93%
See 2 more Smart Citations
“…The EIF2AK4 gene is currently the only gene identified in heritable PVOD/PCH. Besides the heritable form, environmental risk factors such as occupational organic solvent exposure and chemotherapy have been associated with the development of PVOD/PCH [46][47][48].…”
mentioning
confidence: 99%